Impact of autologous transplantation on survival in patients with newly diagnosed multiple myeloma who have high‐risk cytogenetics: A meta‐analysis of randomized controlled trials. Issue 12 (4th April 2022) - Chakraborty, Rajshekhar; Siddiqi, Rabbia; Willson, Gloria; Gupta, Samiksha; Asghar, Noureen; Husnain, Muhammad; Aljama, Mohammed A.; Behera, Tapas Ranjan; Anwer, Faiz; Perrot, Aurore; Riaz, Irbaz B
Abstract : Background: Despite routine evaluation of cytogenetics in myeloma, little is known regarding the impact of high‐dose therapy (HDT) consolidation on overall survival (OS) or progression‐free survival (PFS) in patients who have high‐risk cytogenetics. The authors performed a meta‐analysis of randomized controlled trials (RCTs) to assess the heterogeneity of HDT efficacy according to cytogenetic risk. Methods: All RCTs in patients who had newly diagnosed myeloma from 2000 to 2021 that compared upfront HDT versus standard‐dose therapy (SDT) consolidation were included. The primary objective was to assess the difference in HDT efficacy between standard‐risk and high‐risk cytogenetics in terms of the OS or PFS log(hazard ratio) (HR). The pooled OS and PFS HR was calculated according to cytogenetic‐risk subgroup using a random‐effects model, and heterogeneity ( I 2 ) (the percentage of total observed variability explained by between‐study differences) was assessed using an interaction test. Results: After screening 3307 citations, 6 RCTs were included for PFS analysis, and 4 were included for OS analysis. The median follow‐up ranged from 3.1 to 7.8 years. The pooled OS HR for HDT versus SDT consolidation in patients with standard‐risk and high‐risk cytogenetics was 0.90 (95% confidence interval [CI], 0.70‐1.17; I 2 = 0%) and 0.66 (95% CI, 0.45‐0.97; I 2 = 0%), respectively. The difference in HDT efficacy in terms of OS between standard‐risk and high‐risk patients was statistically significant in favor of the high‐risk group ( P for interaction = .03). The pooled PFS HR for HDT versus SDT was 0.65 (95% CI 0.56‐0.76; I 2 = 0%) versus 0.52 (95% CI, 0.33‐0.83; I 2 = 55%), respectively. The difference in HDT efficacy in terms of PFS between standard‐risk and high‐risk patients was not significant ( P for interaction = .25). Conclusions: The magnitude of OS benefit with upfront HDT is cytogenetics‐dependent. Patients with high‐risk cytogenetics should preferably receive upfront rather than delayed HDT consolidation. Lay Summary: Upfront autologous stem cell transplantation improves overall survival in patients with newly diagnosed myeloma harboring high‐risk cytogenetics. Abstract : The progression‐free survival benefit of upfront autotransplantation in patients with myeloma was similar irrespective of cytogenetic‐risk subgroup. The overall survival benefit of upfront autotransplantation in myeloma was predominantly derived by patients who had high‐risk cytogenetics.